Poor or fair self-rated health is associated with depressive symptoms and impaired perceived physical health: A cross-sectional study in a primary care population at risk for type 2 diabetes and cardiovascular disease - Ansa Talvikki Rantanen; Jyrki Jaakko Antero Korkeila; Hannu Kautiainen; Päivi Elina Korhonen (TAYLOR & FRANCIS LTD, 2022)
Background: Psychosocial factors such as depressive symptoms should be considered when assessing cardiovascular (CV) risk. Depressive symptoms are suggested to be associated with poor perception of one's health, i.e. self-rated health (SRH). Thus, assessing SRH could be a practical tool in CV risk prediction. However, SRH may also emphasize physical, mental or social aspects. Objectives: To assess the relationship of SRH and depressive symptoms, classic CV risk factors and perceived physical health among persons at risk for type 2 diabetes (T2D) and cardiovascular disease (CVD). Methods: In this cross-sectional study in a primary care population, 2555 persons (mean age 58 +/- 7, 56% women) at risk for T2D or CVD were evaluated. Generalized linear statistical models were used to evaluate the association of depressive symptoms (Beck's Depression Inventory score >= 10), CV risk factors, and perception of SRH and physical health (assessed by Short Form Health Survey). Results: Poor or fair health was reported by 40% of the participants. They had more unhealthy lifestyle habits and CV risk factors than subjects rating their health as at least good. Among those with poor or fair SRH, the prevalence of depressive symptoms was 36% and associated with perception of physical health. Conclusion: Poor SRH is associated with depressive symptoms and impaired perceived physical health. Assessing SRH might be useful for detecting possible depressive symptoms in patients in CV risk management and diabetes care.